A double‐blind, placebo‐controlled study to assess the effect of a probiotic mixture on symptoms and inflammatory markers in women with diarrhea‐predominant IBS. Issue 7 (8th March 2017) - Hod, K.; Sperber, A. D.; Ron, Y.; Boaz, M.; Dickman, R.; Berliner, S.; Halpern, Z.; Maharshak, N.; Dekel, R.
Abstract: Background: Micro‐inflammation is considered an element in the pathogenesis of irritable bowel syndrome (IBS). High‐sensitivity C reactive protein (hs‐CRP) was previously shown to be higher in IBS compared to healthy controls, albeit within the normal range. Since probiotics may suppress micro‐inflammation in the gut, we tested if they reduce symptoms and inflammatory markers (hs‐CRP and fecal calprotectin (FC) in diarrhea‐predominant IBS (IBS‐D). The aim of this study was to assess the clinical and laboratory effects of BIO‐25, a multispecies probiotic, in women with IBS‐D. Methods: A double‐blind, placebo‐controlled study. Following a 2‐week run‐in, eligible women were assigned at random to a probiotic capsule or an indistinguishable placebo, twice daily for 8 weeks. IBS symptoms and stool consistency were rated daily by Visual Analogue Scales (VAS) and the Bristol Stool Scale (BSS). High‐sensitivity C reactive protein was tested at baseline, 4 and 8 weeks. FC was tested at baseline and 8 weeks. Key Results: One hundred and seventy‐two IBS‐D patients were recruited and 107 eligible patients were allocated to the intervention (n=54) or placebo (n=53) group. All symptoms improved in both groups with no significant difference between them in symptom improvement, hs‐CRP or FC levels. Conclusions & Inferences: An 8‐week treatment with BIO‐25 improved symptoms in women with IBS‐D, but was not superior to placebo. This rigorously designed and executed study supports the findings of other studies that did not demonstrate superiority of probiotics over placebo in IBS. High quality clinical studies are necessary to examine the efficacy of other specific probiotics in IBS‐D patients since data are still conflicting. Abstract : Our randomized clinical trial demonstrates that an 8‐week treatment with a probiotic mixture (BIO‐25) improved symptoms in women with IBS‐D, but was not superior to placebo. We also did not find any significant changes in hs‐CRP or calprotectin levels. This rigorously designed and executed study supports the findings of other studies that did not demonstrate superiority of other probiotics over placebo in IBS.